Differential effect of monoterpenes and flavonoids on the transcription of aromatic ring-hydroxylating dioxygenase genes in Rhodococcus opacus C1 and Rhodococcus sp. WAY2 - Zubrova, Andrea; Tadrosova, Manuela; Semerad, Jaroslav; Cajthaml, Tomas; Pajer, Petr; Strejcek, Michal; Suman, Jachym; Uhlik, Ondrej (Microbial genomics, 2025)
Aromatic ring-hydroxylating dioxygenases (ARHDs) play a crucial role in the aerobic biodegradation of both natural and anthropogenic aromatic compounds. Although their ability to process contaminants is not entirely understood, it is thought to have evolved from the transformation of structurally similar secondary plant metabolites (SPMs). Hence, to investigate this connection, we tested a variety of SPMs from the monoterpene and flavonoid classes as carbon sources and transcriptional effectors of several phylogenetically distant ARHD genes involved in the degradation of aromatic pollutants. Specifically, we focused on bphA1, nahA1 and phtA1 in Rhodococcus opacus C1, whose genomic analysis is also presented hereinafter, and bphA1a, nahA1-bphA1b and etbA1ab in Rhodococcus sp. WAY2. Whilst induction was only observed with (R)-carvone for bphA1a and nahA1-bphA1b of strain WAY2, and with p-cymene for nahA1 and nahA1-bphA1b of strains C1 and WAY2, respectively, an extensive inhibition by flavonoids was observed for most of the genes in both strains. To the best of our knowledge, our study is the first to report the effect of flavonoids and monoterpenes on the transcription of nahA1, etbA1 and phtA1 genes. In addition, we show that, in contrast to pseudomonads, many flavonoids inhibit the transcription of the ARHD genes in rhodococci. Thus, our work provides a new perspective on flavonoids as the transcriptional effectors of ARHDs, highlighting the significant variability of these enzymes and the divergent responses that they elicit. Moreover, our results contribute to understanding the complex interactions between microorganisms and SPMs and provide insights into the molecular basis of a number of them.
Keywords: aromatic pollutants; Dioxygenases; biodegradation; Rhodococcus; aromatic ring-hydroxylating dioxygenases; Monoterpenes; Gene Expression Regulation, Bacterial; monoterpenes; Biodegradation, Environmental; biodegradace; Transcription, Genetic; genetická transkripce; flavonoidy; Bacterial Proteins; monoterpeny; dioxygenasy; Flavonoids; fylogeneze; regulace genové exprese u bakterií; bakteriální proteiny; Phylogeny; flavonoids